Rzeczowniki złożone o strukturze NN i VN we włoskim słownictwie piłkarskim. Nowe tendencje słowotwórcze we współczesnym języku włoskim - Szemberska, Anna (My University, 2013)
The PhD thesis presents the main tendencies in Noun compounding in Modern Italian on the example of Italian football column that is NN and VN compounds. The thesis aims in particular at exploring compound nouns NN and VN and their types. The goal is not only to establish the most frequent tendency in nominal compounding in Italian, but also to define the role of English elements, seldom heads of such compounds. The language material which comes from Italian website of the daily “La Gazzetta dello Sport” (1997-2010). Drawing on Thornton’s (2007), Dardano’s (1996) theory of mental lexicon and von Humboldt’s (2001), Sapir’s (1951) and Whorf’s (1982) theory of linguistic picture of the world of a linguistic community, the autor analyzes 4 types of compounds: NN subordinate compounds, NN attributive compounds, NN coordinate compounds and VN exocentric compounds.The author has collected a corpus of data totaling 329 compound nouns. We analyze Italian lexicon and word formation in Italian, lexical productivity, lexical density and also the phenomenon of neologisms and occasionalisms. The corpus data confirm our hypothesis: NN and VN compounds are productive in Modern Italian.

La tesi è strutturata in quattro capitoli riguardanti l’analisi dei composti NN e VN nel lessico delle rubriche calcistiche italiane. Dallo studio risulta che il Nome si trova al centro dei processi creativi e costituisce il nucleo della formazione delle parole. I risultati dell’analisi confermano la produttività dei composti a schema NN e VN nonché i cambiamenti che vanno avvenendo nelle società di oggi (i composti NN per coordinazione che designano persone od oggetti aventi due funzioni: portieri protagonisti, palle-sponde, cross rasoterra) ed il dato di fatto che di fronte al mutare della società la lingua non resta passiva.La maggioranza dei composti del corpus (i composti per subordinazione e quelli per attribuzione) sono composti formati tramite la regola produttiva nell’italiano contemporaneo conformememente alla quale le regole di composizione danno i composti endocentrici con testa a sinistra.

W rozprawie doktorskiej zatytułowanej „I Nomi composti NN e VN nel lessico calcistico italiano. Aspetti e tendenze della creatività lessicale nell’italiano contemporaneo” („Rzeczowniki złożone o strukturze NN i VN we włoskim słownictwie piłkarskim. Nowe tendencje słowotwórcze we współczesnym języku włoskim”) analizie poddane zostały sprawozdania pomeczowe, które ukazały się na łamach internetowego wydania La Gazzetta dello Sport w latach 1997-2010. Zagadnienie kreatywności leksykalnej zostało ujęte przez pryzmat teorii Chomsky'ego (1970) i słownika mentalnego (Graffi, Scalise 2003; Peressotti, Job 2006; Berruto 2006), jak również koncepcję analogie créatrice (Sypnicki 1979). Niesprzeczna z wyżej wymienionymi jest teoria, że słowotwórstwo danego języka nieustannie współtworzy i kształtuje językowy obraz świata danej społeczności językowej (Humboldt 2001, Sapir 1951, Whorf 1982, Jamrozik 2005, Gołąb 2004, Szczyszek (w druku). Analiza 329 zarejestrowanych rzeczowników złożonych podzielonych w zależności od relacji pomiędzy członami na rzeczowniki złożone podrzędnie (Nomi composti per subordinazione), rzeczowniki złożone atrybutywnie (Nomi composti per attribuzione), rzeczowniki złożone współrzędnie (Nomi composti per coordinazione) oraz rzeczowniki złożone egzocentryczne (Nomi composti esocentrici) potwierdziła hipotezę, że rzeczowniki o schemacie NN i VN są formami produktywnymi we współczesnym włoskim.
Noun-Noun and Verb-Noun compounds in Italian Football Lexicon. Aspects and tendencies of the lexical creativity in Modern Italian
I nomi composti NN e VN nel lessico calcistico italiano. Aspetti e tendenze della creatività lessicale nell'italiano contemporaneo
Wydział Neofilologii: Instytut Filologii Romańskiej, Zakład Języka Włoskiego
Keywords: Rzeczowniki złożone; Compound nouns; Nomi composti; Kreatywność leksykalna; Lexical creativity; Creatività lessicale; Słownik mentalny; Mental lexicon; Lessico mentale; Kompozycja; Compounding; Composizione; Język piłki nożnej; Language of football; Lessico calcistico